Efikasi Vaksinasi pada Benih Ikan Nila (Oreochromis niloticus) dengan Metode Infiltrasi Hiperosmotik untuk Mencegah Infeksi Streptococcus agalactiae (THE EFFICACY OF VACCINATION ON TILAPIA SEEDS OF (Oreochromis niloticus) USING HYPEROSMOTIC INFILTRATION - Firdausi, Amalia Putri; Sukenda, Sukenda; Nuryati, Sri (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.634, 2018)
The objective of this study was to evaluate the effectiveness of vaccination on tilapia seedlings resulted from the vaccinated parent by hyperosmotic infiltration method at four different salinity to prevent Streptococcus agalactiae bacterial infection. A total of 100 seeds aged 20 days from the vaccinated mother were immersed in four different salinity: 0 ppt (control), 10 ppt, 20 ppt, and 30 ppt for five minutes, then removed and transferred into vaccine-containing containers for 30 minutes. Further maintenance was performed in freshwater aquariums and at days 10, 20, and 30 post vaccination, the immune system performance: Relative Percent Survival (RPS) after the challenge test, specific antibody level, and lysozyme was observed. The study was conducted using a complete randomized design with three replications. The results showed that the 10 ppt salinity treatment gave the best results compared to the others and control. The final RPS (10 ppt) value was 84.72%, 66.49%, and 47.06%, on the 10th, 20th, and 30thh days of vaccination, respectively. Specific antibody levels (10 ppt) were 0.077, 0.078, and 0.077 and lysozyme 0.092, 0.084, and 0.032 at days 10, 20, and 30 post vaccination, respectively. The value of RPS and specific antibody level at 10 ppt salinity was significantly different (P <0.05) compared to the other treatments, while the lysozyme treatment activity of 10 ppt was not significantly different compared to the 20 ppt treatment. Vaccination using 10 ppt saline hyperosmotic infiltration can improve the performance of the immune system by improving maternal immune protection against Streptococcus agalactiae infection.